Rekayasa Chitosan Sebagai Pengawet dan Meningkatkan Kadar Protein Dalam Tahu [Technologi Engineering Chitosan As A Preservative and Elevated Levels Of A Protein On Tofu ] - Sapto Andriyono; Crhisnawati Vega; Daniel Elkana; Oktavia Putri; Rikky Leonard (Jurnal Ilmiah Perikanan dan Kelautan, 2013)
Abstract Chitosan is the potential to serve as a food preservative, because chitosan has polikation positively charged so that it can inhibit the growth of microbes and are able to bind to the compounds negatively charged such as protein, polysaccharides, nucleid acid, heavy methal and others. In addition, molecules of chitosan has an N capable of forming amino compound which is a component of protein and amine moieties on the H atoms which facilitates chitosan interact with water through hydrogen bonds. Know who manufactured this process at the time of processing is still done traditionality. So that power save know produced has a fairy low level of durability. This study used a randomized complete design methods, experimental design was used with tree treatment with five replicate. Treatment imposed in the research include ; treatment with the awarding of chitosan as much as 1%, granting of chitosan treatment B as much as 2%, granting of chitosan treatment C by as much as 3%. Form the results of our study, obtained a good treatment doses for food out of 3%. The doses may be extend save out to 5 days in the future at room temperature and increase the levels of protein know 0,5 – 1,5 %.